Knowledge, Attitudes and Practices toward Melioidosis among Nursing and Plant Science Students at International Islamic University Malaysia (IIUM): A Cross-Sectional Study - Nurbasirah Ahmad Zaiki@Ahmad Zaki; Mirshahirah Aini Sahruddin Sah; Revathy Arushothy; Azmir Ahmad; Mohd Hanif Jainlabdin (INTERNATIONAL JOURNAL OF CARE SCHOLARS, 2026)
Background: Melioidosis is an endemic but neglected tropical disease in Malaysia, particularly in Pahang. This study hypothesised that nursing students would demonstrate significantly higher knowledge of melioidosis than plant science students due to differences in disciplinary training, while attitudes and preventive practices would be comparable. This cross-sectional study aimed to assess and compare the knowledge, attitudes, and practices toward melioidosis among plant science and nursing students at IIUM. Methods: A cross-sectional study was conducted among 264 nursing and plant science undergraduate students at the International Islamic University Malaysia (IIUM), Kuantan. Data were collected using a structured self-administered questionnaire and analysed using descriptive statistics and the Mann–Whitney U test (p < 0.05). Results: Nursing students demonstrated significantly higher knowledge scores than plant science students (U = 1849.0, p = 0.020). No significant differences were observed in attitude (p = 0.490) or preventive practice (p = 0.960). Overall, nursing students exhibited moderate-to-high knowledge levels, whereas plant science students were more frequently classified as having low knowledge. Both groups demonstrated generally positive attitudes and favourable preventive practices. Conclusion: Nursing students possessed better knowledge of melioidosis, supporting the hypothesis that discipline-specific education influences disease awareness. Integrating melioidosis education into healthcare- and agriculture-related curricula through a One Health approach may strengthen awareness and preparedness among future professionals in endemic regions.